2014
DOI: 10.1093/icvts/ivu080
|View full text |Cite
|
Sign up to set email alerts
|

In patients with resectable non-small-cell lung cancer, is video-assisted thoracoscopic segmentectomy a suitable alternative to thoracotomy and segmentectomy in terms of morbidity and equivalence of resection?: Table 1:

Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was 'In patients with resectable non-small-cell lung cancer, is video-assisted thoracoscopic segmentectomy a suitable alternative to thoracotomy and segmentectomy in terms of morbidity and equivalence of resection?' Altogether 232 papers were found as a result of the reported search, of which 7 represented the best evidence to answer the clinical question. The authors, journal, date and country of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…A systematic review considering either retrospective comparative studies or prospective observational studies has concluded that anatomic video thoracoscopic segmentectomy is a feasible operation with at least equivalent levels of morbidity, recurrence, and long-term survival compared with open segmentectomy. 11 Furthermore, several studies report significant differences in the length of hospital stay, postoperative complications, and duration of chest tube placement, suggesting that in selected cases, thoracoscopic segmentectomy may confer additional perioperative benefit compared with the thoracotomy procedure. 11 Moreover, a recent retrospective study comparing thoracoscopic segmentectomy with thoracoscopic lobectomy after propensity-score matching has shown equal short-term surgical results and long-term oncologic outcomes between the two procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review considering either retrospective comparative studies or prospective observational studies has concluded that anatomic video thoracoscopic segmentectomy is a feasible operation with at least equivalent levels of morbidity, recurrence, and long-term survival compared with open segmentectomy. 11 Furthermore, several studies report significant differences in the length of hospital stay, postoperative complications, and duration of chest tube placement, suggesting that in selected cases, thoracoscopic segmentectomy may confer additional perioperative benefit compared with the thoracotomy procedure. 11 Moreover, a recent retrospective study comparing thoracoscopic segmentectomy with thoracoscopic lobectomy after propensity-score matching has shown equal short-term surgical results and long-term oncologic outcomes between the two procedures.…”
mentioning
confidence: 99%
“…11 Furthermore, several studies report significant differences in the length of hospital stay, postoperative complications, and duration of chest tube placement, suggesting that in selected cases, thoracoscopic segmentectomy may confer additional perioperative benefit compared with the thoracotomy procedure. 11 Moreover, a recent retrospective study comparing thoracoscopic segmentectomy with thoracoscopic lobectomy after propensity-score matching has shown equal short-term surgical results and long-term oncologic outcomes between the two procedures. 12 In conclusion, it is now clear that although segmentectomy is still largely reserved for patients with compromised cardiopulmonary status, recent evidence supports the intentional use of such an operation even in low-risk patients with tumors < 2 cm.…”
mentioning
confidence: 99%
“…Sublobar resection (segmentectomy or wedge resection) is recommended for patients with stage I ground glass opacity ≤2 cm (3). The long-term oncologic efficiency of segmentectomy versus lobectomy for small NSCLC has yet to be demonstrated (4).…”
Section: Introductionmentioning
confidence: 99%
“…Although segmentectomy can preserve lung function, its non-inferiority regarding the oncological outcome is still a matter of debate (1)(2)(3)(4). Surgical approaches such as video-assisted thoracoscopic surgery (VATS) and robotic surgery have also been reported for segmentectomy (5)(6)(7)(8). In addition to primary lung cancer, segmentectomy is performed for metastatic lung lesions arising from other malignancies such as colon cancer (9,10).…”
Section: Introductionmentioning
confidence: 99%